KINERJA AGRIBISNIS SAPI POTONG RAKYAT DI PROVINSI JAWA TIMUR: DAMPAK KRISIS MONETER DAN IMPLEMENTASI KEBIJAKAN OTONOMI DAERAH - MAYROWANI, HENNY (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006)
In the period of 1995 - 2002, domestic cattle agribusiness in East Java has indicated an unpleasant condition, the growth of production, consumption and trade tend to decrease around 1.5 - 4.7 percent a year. Meanwhile, nominal price of feed and livestock products have increased more than 8 percent. Although, the real prices were increasing only around 0.5 - 1.4 percent a year. Economic crisis affect significantly the decreasing of the household income, it has an impact in reducing of the volume of East Java cattle distribution to outer region. This condition become worse by reduction of cattle population growth and competition with live cattle import and their products. In 1995-2002 and during the regional autonomy policy implementation process, cattle population growth has decreased - 1.71 and - 24.85 percent a year respectively. Generally, decreasing of cattle population growth has related to reduction of cattle herd that no longer used in intensification of paddy field. Decreasing of cattle population growth during the regional autonomy policy implementation process were caused by three reasons, such as: (1) Lack of local government ability to increase the development of breeding and fattening business that related to the budget and government management problems; (2) Market demand of cattle from outer region was decreasing; and (3) The real price of breed and fattening cattle was not attractive for farmers to carry on in their business. Based on those problems above, in order to develop domestic cattle agribusiness, it is necessary to develop: (1) The policy which able to consolidate the central, province, and district government in implementing integration programs; (2) Reducing market distortion policies; (3) Provide protection and special treatment for small scale farmers to face global trade liberalization; and (4) Institutional reform of domestic cattle agribusiness.
Keywords: Economic Crisis, Regional Autonomy, Agribusiness, Cattle.